Embryonic stem cell self‐renewal pathways converge on the transcription factor Tfcp2l1. (13th August 2013) - Ye, Shoudong; Li, Ping; Tong, Chang; Ying, Qi‐Long
<x xml:space="preserve">Abstract</x> Mouse embryonic stem cell (mESC) self‐renewal can be maintained by activation of the leukaemia inhibitory factor (LIF)/signal transducer and activator of transcription 3 (Stat3) signalling pathway or dual inhibition (2i) of glycogen synthase kinase 3 (Gsk3) and mitogen‐activated protein kinase kinase (MEK). Several downstream targets of the pathways involved have been identified that when individually overexpressed can partially support self‐renewal. However, none of these targets is shared among the involved pathways. Here, we show that the CP2 family transcription factor Tfcp2l1 is a common target in LIF/Stat3‐ and 2i‐mediated self‐renewal, and forced expression of Tfcp2l1 can recapitulate the self‐renewal‐promoting effect of LIF or either of the 2i components. In addition, Tfcp2l1 can reprogram post‐implantation epiblast stem cells to naïve pluripotent ESCs. Tfcp2l1 upregulates Nanog expression and promotes self‐renewal in a Nanog‐dependent manner. We conclude that Tfcp2l1 is at the intersection of LIF‐ and 2i‐mediated self‐renewal pathways and plays a critical role in maintaining ESC identity. Our study provides an expanded understanding of the current model of ground‐state pluripotency.